Excess dose-related parameters (Vex, Rex, and iRex): novel predictors and late toxicity correlations in cervical cancer image-guided adaptive brachytherapy - Prasartseree, Tissana (J Contemp Brachytherapy, 2020)
PURPOSE: In this paper, excess dose is originally proposed to represent the dose outside the target volume that encompass only organs at risk (OARs), not the whole dose volume of isodose surface volume (ISV). By means of spatial consideration, excess dose-related parameters would also compensate inconsistent applicator positions and OARs motion, which may deviate the identical dose small-volume assumption of D(2cc). Late toxicity correlations of these parameters were investigated. MATERIAL AND METHODS: A retrospective review was performed on cervical cancer high-dose-rate image-guided adaptive brachytherapy (HDR-IGABT). From ISVs of 60 to 100 Gy EQD(2) (a/β = 3), excess dose-related parameters were derived as following: toxicity negligible volume (Vneg = V(60) of toxicity negligible organs; high-risk clinical target volume – HR-CTV, uterus, and vagina), excess dose volume (Vex = ISV – Vneg), Vneg normalized parameters of excess dose volume ratio (Rex = Vex/Vneg), and indirect excess dose volume ratio (iRex = ISV/Vneg). Relationships between toxicity and these parameters were analyzed using a mean difference and a probit analysis method. Net reclassification indices (NRIs) were used to compare iRex60 and D(2cc) gastrointestinal (GI) toxicity prediction. RESULTS: From 143 cases with an incidence of 34.9% and 10.5% of 3-year grade 2-4 GI and genitourinary (GU) toxicity, respectively, comparisons of means showed significant difference between grade 0-1 and 2-4 toxicities for late GI toxicity for all parameters, except ISV. There was a dose-response relationship with toxicity for each parameter across the range of 60-100 Gy EQD(2). ED(10) of iRex60 and iRex70 were 2.1 and 1.2, respectively. By comparing iRex60 and D(2cc), additive and absolute NRIs were +6.45 and +7.69%, respectively. The reclassification significantly occurred in range of 65-75 Gy of rectum D(2cc). CONCLUSIONS: Excess dose-related parameters, including Vex, Rex, and iRex, showed significant mean differences and parameter-toxicity relationships for late GI but not for GU toxicities. Positive NRIs suggest iRex60 utilization for spatial control of dose expansion, in addition to high-dose control with OAR small volumes. Further investigations are needed to define the optimum use of these predictors.